Pelatihan Caring terhadap Perilaku Memberikan Asuhan Keperawatan pada Mahasiswa - Yessi Fadriyanti; Zulharmaswita Zulharmaswita; Yosi Suryarinilsih; Heppi Sasmita; Defiaroza Defiaroza (Jurnal Keperawatan Silampari, 2020)
This study aimed to determine the effect of caring training on the behavior of providing nursing care to students of the Poltekeks Kemenkes Padang. The design used in this study was a quasi-experimental pre-post test control group. The results showed that knowledge's p-value, affective, and psychomotor variables = 0.000 (p <0.05). In conclusion, caring training can improve students' experience, affective, and psychomotor in providing nursing care. Keywords: Nursing Care, Caring